Handbook of research on quality assurance and value management in higher education - Nuninger, Walter, 1969-; Chatelet, Jean-Marie, 1951- (A volume in the advances in educational marketing, administration, and leadership (AEMAL) book series, 2016)
"This book is a reference source for the latest scholarly research on quality management and assurance programs and standards in college-level environments, highlighting global perspectives on academic and professional learning"--